Reflections on constitutional law - Anastaplo, George, 1925-2014 (University Press of Kentucky, 2006)
In a trend that disturbs nationally known constitutional scholar George Anastaplo, law schools now place very little emphasis on the study of the United States Constitution as a document. Today, many constitutional law professors spend less than a week teaching the history, philosophical tenets, and legal origins of the Constitution itself and more time on Supreme Court cases. In Reflections on Constitutional Law, Anastaplo emphasizes the continuing significance and importance of the Constitution by examining the most important influences on the American constitutional system, including the Magna Carta and the Declaration of Independence. According to Anastaplo, a rigorous understanding of the Constitution is crucial to comprehending the true meaning of Supreme Court decisions.